Homologous cancer cell membrane-camouflaged nanoparticles target drug delivery and enhance the chemotherapy efficacy of hepatocellular carcinoma. (1st April 2023) - Wu, Yahui; Zhu, Rongtao; Zhou, Mengyang; Liu, Jingjing; Dong, Kai; Zhao, Senfeng; Cao, Jiahui; Wang, Weijie; Sun, Chenguang; Wu, Shitao; Wang, Fan; Shi, Yupeng; et al.
Abstract: Hepatocellular carcinoma (HCC) is a common digestive tract malignancy that seriously threatens human life and health. Early HCC may be treated by intervention, surgery, and internal radiotherapy, while the choice for late HCC is primarily chemotherapy to prolong patient survival. Lenvatinib (LT) is a Food and Drug Administration (FDA)-approved frontline drug for the treatment of advanced liver cancer and has achieved excellent clinical efficacy. However, its poor solubility and severe side effects cannot be ignored. In this study, a bionic nanodrug delivery platform was successfully constructed. The platform consists of a core of Lenvatinib wrapped with a pH-sensitive polymer, namely, poly(β-amino ester)-polyethylene glycol-amine (PAE-PEG-NH2 ), and a shell formed by a cancer cell membrane (CCM). The prepared nanodrugs have high drug loading capacity, long-term stability, good biocompatibility, and a long retention time. In addition, the targeting effect of tumor cell membranes and the pH-responsive characteristics of the polymer materials enable them to precisely target tumor cells and achieve responsive release in the tumor microenvironment, which makes them suitable for effective drug delivery. In vivo experiments revealed that the nanodrug showed superior tumor accumulation and therapeutic effects in subcutaneous tumor mice model and could effectively eliminate tumors within 21 days. As a result, it opens up a new way to reduce side effects and improve the specific therapeutic effect of first-line clinical medications to treat tumors. Highlights: Nanoparticles can improve the solubility of clinical chemotherapy drug LT and drug utilization. Biomimetic nanodrugs with homologous tumor cell membranes have high targeting. pH-sensitive nanocarriers can achieve controlled drug release and reduce side effects. Compared with simple chemotherapy drugs, nanodrugs can significantly improve the tumor treatment effect.